The relationship between information processing style and information seeking, and its moderation by affect and perceived usefulness: Analysis vs. procrastination. (January 2015) - Soane, Emma; Schubert, Iljana; Lunn, Rebecca; Pollard, Simon
Highlights: We examined food safety decision processing of 2960 UK adults. Analytical information processing was associated with more information seeking. Heuristic information processing was associated with less information seeking. Participants who delay decisions sought information when they found it useful. However, anxiety reduced the likelihood of such procrastination. Abstract: We examined the relationship between information processing style and information seeking, and its moderation by anxiety and information utility. Information about Salmonella, a potentially commonplace disease, was presented to 2960 adults. Two types of information processing were examined: preferences for analytical or heuristic processing, and preferences for immediate or delayed processing. Information seeking was captured by measuring the number of additional pieces of information sought by participants. Preferences for analytical information processing were associated positively and directly with information seeking. Heuristic information processing was associated negatively and directly with information seeking. The positive relationship between preferences for delayed decision making and information seeking was moderated by anxiety and by information utility. Anxiety reduced the tendency to seek additional information. Information utility increased the likelihood of information seeking. The findings indicate that low levels of anxiety could prompt information seeking. However, information seeking occurred even when information was perceived as useful and sufficient, suggesting that it can be a form of procrastination rather than a useful contribution to effective decision making.